Carbapenem resistance crisis: a retrospective investigation of gram-negative bacterial isolates in a tertiary care hospital in Egypt - Kotkata, Fedaa A.; Hamed, Nour Alrahman M.; Daoud, Omnia E.; Turky, Amira S.; Tawfik, Marwa I.; Elmorsy, Mariam E.; Al-Barbary, Nermeen H.; Hassan, Mahmoud M.; Mohammed, Mahmoud N.; Sharkawi, Marwa S.; Sayed, Mahmoud M. El; Shamseya, Reem M.; et al. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: The increasing prevalence of carbapenem-resistant gram-negative bacteria poses a significant threat to public health worldwide. This study aimed to investigate the patterns and determinants of carbapenem resistance among gram-negative bacterial isolates from patients admitted to Tanta University Chest Hospital, Egypt. Methods: A retrospective, observational study was conducted, involving patients who received carbapenem antibiotics (ertapenem, imipenem, or meropenem) for at least 48 hours during their hospitalization between January 1, 2023, and December 31, 2023. Data on patient demographics, duration and indication of use and microbiological data were collected. Carbapenem resistance was assessed using antimicrobial susceptibility testing. Results: A total of 80 patients with gram-negative bacterial cultures were included in the study. The overall prevalence of carbapenem resistance was 70%. No significant associations were found between carbapenem resistance and gender, age or indication. However, significant differences in resistance rates were observed among bacterial species. Acinetobacter (87%), Klebsiella (82%), and Pseudomonas (78%) exhibited high probabilities of carbapenem resistance, while E. coli had a lower resistance rate (31%). Logistic regression analysis confirmed that E. coli was significantly less likely to be resistant to carbapenems compared to Pseudomonas (p=0.039, OR=0.127, 95% CI: 0.018-0.905). Conclusions: The study revealed an alarmingly high prevalence of carbapenem resistance among gram-negative bacterial isolates in a tertiary care hospital in Egypt. Effective antimicrobial stewardship programs, strict infection control measures, and continuous surveillance of antimicrobial resistance patterns are crucial to combat the growing threat of carbapenem-resistant organisms.